Increase of bone marrow lymphocytes in systemic mastocytosis: reactive lymphocytosis or malignant lymphoma? Immunohistochemical and molecular findings on routinely processed bone marrow biopsy specimens. Issue 8 (30th July 2003) - Horny, H-P; Lange, K; Sotlar, K; Valent, P
Abstract : Aims : To clarify the nature (reactive or neoplastic) of lesional, perifocally aggregated lymphocytes in bone marrow infiltrates of systemic mastocytosis (SM), the histopathology of which can resemble malignant lymphoma with focal bone marrow involvement, particularly low grade malignant B cell lymphoma of lymphoplasmacytic immunocytoma subtype, which frequently exhibits increased mast cell (MC) numbers. Methods : Thirteen cases of SM and three of lymphoplasmacytic immunocytoma with predominant focal bone marrow infiltration were investigated. Immunostaining of formalin fixed, paraffin wax embedded bone marrow specimens was performed using antibodies against CD2, CD5, CD20, CD23, and CD25; κ and λ immunoglobulin light chains; and MC markers chymase, tryptase, and CD117 (KIT). Monoclonal rearrangements of IgH and TCRγ were studied using seminested polymerase chain reaction (PCR). c-kit point mutation Asp816-Val was detected by PNA mediated PCR clamping and hybridisation probes. Results : The lymphocytic clusters in SM contained nearly equal numbers of mature T and B cells, the latter with no coexpression of aberrant antigens, such as CD5 or CD23. Most MCs in SM cases constantly coexpressed tryptase, CD25, and CD117. No monoclonal rearrangements were seen for IgH or TCRγ. In contrast, B cells from immunocytomas showed light chain restriction and monoclonal rearrangement for IgH, confirming their neoplastic nature. c-kit point mutation Asp816-Val was found in ten of 13 SM cases, but in none of the three immunocytomas. Conclusions : Focal accumulations of lymphocytes in the bone marrow of SM are reactive in nature and could be termed lymphocytosis. A diagnosis of SM-AHNMD/immunocytoma should not be made.